(untitled) (Global Journal of Medical Research, 2020)
Most urinary tract infections are due to Candida species, C. albicans being most prevalent. Laboratory research study was used to examine the prevalence of candidiasis amongst undergraduate students of Chukwuemeka Odumegwu Ojukwu University, Uli. A total of 100 students were investigated. Clean catch midstream urine samples were used for the analysis. Standard microbiological procedures were utilized. A structured questionnaire was issued to each student to obtain their socio-demographic data. Our study found Candida albicans in 14(14%) of the urine samples. Significant candidiasis was strongly associated with being female as higher percentage of the isolates were from female students. Of the 14(14.0%) positive urine samples, 4(28.6%) were from symptomatic students, whereas 10(71.4%) were asymptomatic.